Antara Bantuan dan Ketergantungan: Literatur Review Pengaruh AI terhadap Kognisi Peserta Didik - Muhammad Dirzi Adari; Mega kencana; Suci Fajrina (Advances In Education Journal, 2025)
Development of artificial intelligence (AI) has brought significant changes to the learning process and has influenced students’ cognitive development. This article reviews several recent studies from 2023 to 2025 that examine the impact of AI on learning motivation, memory, critical thinking, and creativity, using a literature review approach to identify the benefits, risks, and strategies for optimizing AI utilization in educational contexts. The review findings indicate that AI can enhance engagement, personalized learning, and information access efficiency, while also supporting the development of critical thinking and creativity through human-AI collaboration. However, excessive dependence on AI may reduce memory training, analytical skills, and individual creative potential. Therefore, teacher guidance and digital literacy are essential factors to ensure balanced and effective AI use. Overall, this study emphasizes that AI has the potential to strengthen students’ motivation and cognition if strategically integrated, providing a foundation for educators and policymakers to design safe, balanced AI-based learning interventions that foster higher-order thinking skills. Keywords: artificial intelligence, cognition, creativity, critical thinking, learning motivation